STRATEGI PENGEMBANGAN AGRIBISNIS NENAS DI KABUPATEN KUBU RAYA KALIMANTAN BARAT - Eva Dolorosa, Melati Fitri, Erlinda Yurisinthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
This research was conducted in the purpose to understand 1) the internal strategic factors which are the strength and the weakness as well as the external strategic factors which are the opportunity and the threat related to the development of pineapple agribusiness in Kubu Raya Regency, West Kalimantan, 2) to determine the alternative strategy that can be applied for the development of pineapple agribusiness in Kubu Raya Regency, West Kalimantan. This research is a descriptive study. The method used in this research is survey and the correspondents were determined with the purposive sampling method consisting bureaucrats, academics, farmers, and related traders. The result of the research shows that the main strength factor is the availability of a proper pineapples cultivation manual (score: 0.4898). The main weakness factor is unefficient management farmer system (score: 0.2117). The main opportunity factor is the availability of a sustainable development program and the main threat factor is the competitiveness of the product with imported fruits which was still low (score 0.2016). Based on the analysis there are six alternative strategies for the development of pineapples agribusiness in Kubu Raya Regency, West Kalimantan, i.e., 1) the enhancement of pineapple production through training and counseling based on Good Agricultural Practices (GAP) and Standar Operational Procedure (SOP) as well as an expansion of the planting area; 2) the enhancement and control of the quality of the product; 3) The enhancement of the production system efficiency; 4) the control of the production from a pest infestation; 5) Developing a partnership pattern and; 6) developing agricultural institutions function. Keywords: Pineapple agribusiness, strategic external factor, strategic internal factor, strategy.